Analysis Of Elementary School Students' Difficulties In Solve Mathematical Questions On Object Weight Measurement Material - Simamora, Aurora Novena; Simanungkalit , Gracia Citra Lavenia; Manurung , Nazwa Audina; Simanjorang , Gabriel Depany; Mailani, Elvi; Rarastika , Nur (Yana Research, 2024)
The ability to measure the weight of objects is a skill needed in various fields, such as trade, industry and health. However, various studies mention that many students have difficulty in understanding and solving math problems related to measuring the weight of objects effectively. This study aims to analyze the difficulties faced by grade 6 students of UPT SDN 025 JANJI, Doloksanggul in solving mathematics problems measuring the weight of objects. Researchers made questions in the form of measuring the weight of objects and found various student errors in answering each question. The method used in this research is quantitative research, which is a research method that focuses on the collection, analysis, and interpretation of numerical data. Based on the results of research and analysis conducted by researchers on 13 sixth grade students at UPT SDN 025 JANJI above, students often face various errors in solving weight measurement problems, namely (1) errors in reading the problem, (2) understanding information, (3) choosing the right mathematical operation, and (4) performing calculations. Students often face various errors in solving weight measurement problems, including errors in reading the problem, understanding the information, choosing the right mathematical operation, and performing calculations. These errors can be categorized into several types, such as reading errors, comprehension errors, transformation errors, process skill errors, and other errors.